Analisis Perbandingan Metode Beton Site-mix dengan Beton Ready-mix - agus bambang siswanto; M Afif Salim; Aulia Firman N (Jurnal Teknik Sipil Unaya, 2021)
In Indonesia, construction projects still use on site concrete or manual concrete (Site-Mix), but since the establishment of a company that produces ready-mix concrete, users of ready-mix concrete have started to be recognized for the various advantages it offers. It is necessary to research which one is more effective and efficient.The research was conducted in the Integrated Dormitory Development Project at Madrasah Aliyah Negeri 2 Kudus with a research focus on calculating tools based on AHSP districts Kudus and the contractor's Time Schedule used on the project. The work that is calculated includes the concrete used in structural work. The purpose of this research is to make comparisons terms of costs for each method. Find the advantages and disadvantages of each method.The analysis technique in this study begins with determining the volume of concrete requirements based on the contractor's time schedule, then multiplied by the coefficient in the analysis of the unit price of the work in Kudus Regency. So that we find the cost for each.Through the analysis of the research results, there are several conclusions, namely that the ready-mix concrete working method is cheaper. While the site-mix concrete work method is more expensive. This project is price difference Rp79,622,437 or 11% efficiency from price site mix concrete